2020
DOI: 10.1111/resp.13973
|View full text |Cite
|
Sign up to set email alerts
|

Mapping IPF helps identify geographic regions at higher risk for disease development and potential triggers

Abstract: Background and objective The relationship between IPF development and environmental factors has not been completely elucidated. Analysing geographic regions of idiopathic pulmonary fibrosis (IPF) cases could help identify those areas with higher aggregation and investigate potential triggers. We hypothesize that cross‐analysing location of IPF cases and areas of consistently high air pollution concentration could lead to recognition of environmental risk factors for IPF development. Methods This retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 32 publications
1
23
0
Order By: Relevance
“…It is well known that NO 2 is a surrogate of traffic-related exposure [ 68 ]; therefore, the study results provide a strong signal that traffic pollution could be involved in the initiation of the fibrotic process and identify a potentially modifiable risk factor for IPF [ 67 ]. A recent retrospective study aimed to identify environmental risk factors for IPF development [ 69 ]. Using the cross-analysis of the incident cases of the disease in the Catalan region, Spain, and estimated exposure to PM 2.5 over the last decade, authors found a coincidence between IPF patient aggregation and PM 2.5 concentration.…”
Section: Impact Of Air-pollution On Disease Initiation and Health mentioning
confidence: 99%
“…It is well known that NO 2 is a surrogate of traffic-related exposure [ 68 ]; therefore, the study results provide a strong signal that traffic pollution could be involved in the initiation of the fibrotic process and identify a potentially modifiable risk factor for IPF [ 67 ]. A recent retrospective study aimed to identify environmental risk factors for IPF development [ 69 ]. Using the cross-analysis of the incident cases of the disease in the Catalan region, Spain, and estimated exposure to PM 2.5 over the last decade, authors found a coincidence between IPF patient aggregation and PM 2.5 concentration.…”
Section: Impact Of Air-pollution On Disease Initiation and Health mentioning
confidence: 99%
“…The relevant occupational exposures for IPF can be described in more detail than ‘inorganic dust’ 5 . We have recently conducted a case–control study of IPF in Australia to examine occupational and environmental risk factors, 7 utilizing job exposure matrices to assess occupational exposures.…”
mentioning
confidence: 99%
“…The Catalonian study 5 did not age‐adjust the data for this disease, although IPF occurs predominantly in the more elderly. Nor did the authors take into account the illustrated sharp seasonal peaks of PM 2.5 , which might well have been influenced by marked increases in winds off the Mediterranean Sea at these times.…”
mentioning
confidence: 99%
See 2 more Smart Citations